A fungal sirtuin modulates development and virulence in the insect pathogen, Beauveria bassiana. (25th August 2021) - Cai, Qing; Tian, Li; Xie, Jia‐Tao; Huang, Qiu‐Ying; Feng, Ming‐Guang; Keyhani, Nemat O.
Summary: Chromatin transitions are mediated in part by acetylation/deacetylation post‐translational modifications of histones. Histone deacetylases, e.g. sirtuins (Sir‐proteins), repress transcription via promotion of heterochromatin formation. Here, we characterize the Sir2 class III histone deacetylase ( BbSir2 ) in the environmentally and economically important fungal insect pathogen, Beauveria bassiana . BbSir2 is shown to contribute to the deacetylation of lysine residues on H3 and H4 histones. Targeted gene knockout of BbSir2 resulted in impaired asexual development, reduced abilities to utilize various carbon/nitrogen sources, reduced tolerance to oxidative, heat, and UV stress, and attenuated virulence. ΔBbSir2 cells showed disrupted cell cycle development and abnormal hyphal septation patterns. Proteomic protein acetylation analyses of wild type and ΔBbSir2 cells revealed the differential abundance of 462 proteins and altered (hyper‐ or hypo‐) acetylation of 436 lysine residues on 350 proteins. Bioinformatic analyses revealed enrichment in pathways involved in carbon/nitrogen metabolism, cell cycle control and cell rescue, defence and mitochondrial functioning. Critical targets involved in virulence included LysM effector proteins and a benzoquinone oxidoreductase implicated in detoxification of cuticular compounds. These data indicate broad effects of BbSir2 on fungal development and stress response, with identification of discrete targets that can account for the observed (decreased) virulence phenotype.